Research on access schemes of SD-WAN multi-cloud aggregation platform - Jia NIU; Yongming YAN; Qiangen ZHAO; Jiajun MIN; Songyang QI (Dianxin kexue)
A detailed description of the current situation, application, demand analysis, basic functions and application scenarios of the multi-cloud aggregation platform were given, and the advantages of SD-WAN compared with the traditional private line multi-cloud access mode was discussed.The networking projects of multiple SD-WAN accessing multi-cloud aggregation platforms were analyzed, a multi-cloud access scheme combining SD-WAN and dedicated line to realize network link monitoring were proposed.The network quality monitoring function of SD-WAN access to multi-cloud and the monitoring function of SD-WAN on underlay dedicated line under the fusion networking was proposed.Based on the topology design of network architecture combining traditional private line to multi-cloud and segmentalized access mode of SD-WAN and traditional private line to multi-cloud, the application scenarios of hybrid network to multi-cloud was introduced and the value of SD-WAN to multi-cloud was reflected from the perspective of fusion network by combining advantages and disadvantages.